Parent Drug Conceptualizations During Assertiveness Training - Fox, Tricia A. (Canadian Journal of Counselling and Psychotherapy, 2011)
The prevalence of drugs in society has led many parents to seek assistance from parent drug education programs. However, because of environmental influences, and parental characteristics and needs, drug education programs specifically aimed at parents may not be effective in assisting them to cope with drug problems within their families. This paper presents an overview of parent drug education programs together with information regarding those problems, concerns and needs faced by parents who are dealing with an offspring drug user/abuser. The presentation emphasizes the unique, individual characteristics of parents and suggests that these influences may be the main determinants of the effectiveness of parent drug education programs. The influence of parental characteristics on parent drug education programs warrants more research.